A phase II, multicenter, open-label trial to evaluate the safety and efficacy of ISU303 (Agalsidase beta) in patients with Fabry disease. Issue 37 (16th September 2022) - Hwang, Soojin; Lee, Beom Hee; Kim, Woo-Shik; Kim, Dae-Seong; Cheon, Chong Kun; Lee, Chang Hwa; Choi, Yunha; Choi, Jin-Ho; Kim, Ja Hye; Yoo, Han-Wook
Abstract : Background: Fabry disease (FD) is caused by a deficiency in the activity of the lysosomal enzyme, α-galactosidase A (α-Gal A), which leads to globotriaosylceramide (Gb3) deposition in multiple tissues. The current management of FD is enzyme replacement therapy (ERT). We report on the efficacy and safety of a new agalsidase beta, ISU303, in FD. Methods: Ten patients (7 males, 3 females) were enrolled and administered a 1 mg/kg dose of ISU303, every other week for 6 months. The primary endpoint was the normalization of plasma Gb3 level. The secondary endpoints were the changes from baseline in urine Gb3 and the plasma and urine lyso-globotriaosylsphingosine (lyso-Gb3) level. Echocardiography, renal function test, and pain-related quality of life were also assessed before and after administration. Safety evaluation was performed including vital signs, laboratory tests, electrocardiograms, antibody screening tests, and adverse events at each visit. Results: At 22 weeks of treatment, plasma and urine Gb3 level decreased by a mean of 4.01 ± 1.29 μg/mL (range 2.50–5.70) ( P  = .005) and 1.12 ± 1.98 μg/mg Cr. (range 0.04–5.65) ( P  = .017), respectively. However, no significant difference was observed in plasma and urine lyso-Gb3 levels. Echocardiography also was not changed. Renal function and pain-related quality of life showed improvements, but there was no clinical significance. No severe adverse events were observed. Only 1 patient developed an anti-drug antibody without neutralizing activity during the trial. Conclusion: This study showed the efficacy and safety of ISU303. Treatment with ISU303 significantly resulted in plasma and urine Gb3 decrease in patients with FD. These results suggest that ISU303 is safe and effective and can alternative ERT for FD.